Analisis Desain Gedung Imigrasi Kelas I Banda Aceh dari Struktur Baja ke Struktur Beton Bertulang - Alfisyahrin Alfisyahrin; Muhammad Riswandy; Michel Kasaf; Tjut Rizqi Maysyarah Hadi; Mhd. Arief Diana (Yayasan Literasi Sains Indonesia, 2025)
This study provides an understanding of the advantages of reinforced concrete in the construction of multi-story buildings in Banda Aceh. The objective of this research is to improve the efficiency of constructing the Class I Immigration Office Building in Banda Aceh by replacing the main structural system from steel to reinforced concrete. This change was carried out in accordance with the SNI 2847:2019 standard, utilizing the ETABS application for the design and analysis process.The results show that the total building weight in the existing condition (steel structure) is 1,594,043.95 kg, while using reinforced concrete increases the weight to 2,631,222.38 kg. At portal 5-5, the differences in bending moment and shear force between the steel and reinforced concrete structures are significant, with values of -2.9559 kNm and -80.0447 kNm for bending moment, and 3.5657 kN and 29.1996 kN for shear force, respectively. Additionally, the maximum lateral displacement in both X and Y directions is lower in the reinforced concrete structure compared to the steel structure. The axial force at portal 5-5 also shows an increase from -492.0887 kN (steel structure) to -949.2849 kN (reinforced concrete structure). These findings indicate that the use of reinforced concrete provides better stability, capacity, and overall structural performance compared to the steel structure